Tindak Pidana Minuman Khamar dalam Qanun Provinsi Aceh Nomor 12 Tahun 2003 - Syarifuddin Usman (Legitimasi: Jurnal Hukum Pidana dan Politik Hukum, 2012)
Islam forbids his people to do acts that could harm future either again himself, nor to the community and surrounding environment. One of the prohibited acts and should be shunned by a moslem is the act of taking something that fifth major precept, like drinking alcohol. In Islamic law in Aceh Province Qanun Number 12 of 2003, a person who drink alcohol will be subject to maximum caning eighty lashes and least forty lashes. That Qanun will provide a detterent effects and embrassing to the perpetrators, because the punishment was carried out in front of crowds in presence of many people, let one published in the newspapers an television.